Preparation of Fe catalyst coated on activated carbon for decomposition of aqueous phenol in three-phase fluidized bed reactor - Pilasinee Limsuwan (Chulalongkorn University, 2012)
Thesis (M.Eng.)--Chulalongkorn University, 2008